Low haze decay rate flash evaporation material
Patent Information
- Application Number
- JP2025544483
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-07-14
- Filing Date
- 2023-10-07
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-10-07
AI Technical Summary
【0035】 従来の技術と比べて、本発明の優れた効果は、次の通りである。 本発明は、フラッシュ蒸発材料のヘイズ減衰率と遮熱率減衰率は、少なくとも紡糸原料における酸化亜鉛を担持した多孔質炭素材料の含有量、及び紡糸溶媒における界面活性剤の含有量などの要因と密接に関連していることを実験的に見出し、且つ調製されたフラッシュ蒸発材料がより低いヘイズ減衰率と遮熱率減衰率を有するように、新規なフラッシュ蒸発材料の製造プロセスを提供し、それにより、従来技術におけるフラッシュ蒸発材料が一定の期間使用すると、遮熱性能とヘイズ性能が明らかに低下するという問題を克服した。
Smart Images

Figure 0007934050000001
Abstract
Description
[Technical Field]
[0001] The present invention belongs to the field of flash evaporation, and more particularly to flash evaporation materials with low haze decay rates. [Background technology]
[0002] Flash evaporation spinning involves dissolving similar polymers such as PE and PP in a specific spinning solvent to create a spinning solution, which is then ejected from the spinning hole. The rapid evaporation of the solvent re-hardens the polymer into fibers, which are then adsorbed onto a web-forming curtain to directly form a fiber web. Finally, flash material is produced through a hot-pressing and winding process. The current polymer raw material for flash evaporation is PE. Flash evaporation polyethylene nonwoven fabrics possess many excellent properties, including superior waterproofing and breathability. The sheet material has excellent strength, is tear-resistant, puncture-resistant, and burst-resistant. Generally, the sheet material does not shed lint or generate dust, and exhibits excellent performance over a wide temperature range. Therefore, flash evaporation polyethylene nonwoven fabrics are widely used in packaging materials, protective clothing, covers, and printing substrates.
[0003] Chinese Patent Publication No. CN114687057A relates to a flash evaporation sheet and its applications, characterized in that the raw materials are polyethylene and a modifying agent, the bending length degradation value △C is 0.1 to 0.4, △C = 1 - C2 / C1, where C1 is the bending length of an unaged flash evaporation sheet, C2 is the bending length of an aged flash evaporation sheet, and the bending length C2 of the aged flash evaporation sheet is 4 to 10 centimeters. The flash evaporation sheet of this application can maintain brightness, reduce bending length degradation, extend the service life of the product, and expand the range of applications.
[0004] Chinese Patent Publication No. CN114687069A relates to a multifunctional polymer nonwoven fabric and its fabric, characterized in that the rate of decay of its elongation at break ▲E is 0.20 to 0.50, where ▲E = 1 - E2 / E1, where E1 is the elongation at break of the multifunctional polymer nonwoven fabric before aging test treatment, and E2 is the elongation at break of the multifunctional polymer nonwoven fabric after aging test treatment, and the value of E2 is less than 0.5. The process described in this application is simple and widely applicable.
[0005] Chinese Patent Publication No. CN114687068A relates to an improved flash evaporation nonwoven fabric. The invention described in this application addresses the problem in the prior art that flash evaporation nonwoven fabrics lose brightness after a certain period of use, by providing an improved flash evaporation nonwoven fabric in which the D65 fluorescence brightness loss rate ▲F of the improved flash evaporation nonwoven fabric is 0.20 to 0.30, where ▲F = 1 - F2 / F1, where F1 is the D65 fluorescence brightness of the unaged nonwoven fabric and F2 is the D65 fluorescence brightness of the aged nonwoven fabric. The aging process conditions are an irradiance of 60±2 w / m2 in the wavelength range of 300 to 400 nanometers, a black mark temperature of 65±2℃, a test chamber air temperature of 38±3℃, a relative humidity of 50±10%, and a drying time of 1440 hours. The flash evaporation nonwoven fabric of the invention described in this application can maintain high brightness after a certain period of use.
[0006] Chinese Patent Publication No. CN114108112A relates to a polyethylene sheet characterized by a tensile strength aging rate ΔS of 0.10 to 0.30, where ΔS = 1 - S2 / S1, S1 is the tensile strength of the unaged nonwoven fabric in kN / m, and S2 is the tensile strength of the aged nonwoven fabric in kN / m. The aging process conditions are as follows: irradiance in the wavelength range of 300 to 400 nanometers is 60 ± 2 w / m2, black mark temperature is 65 ± 2 °C, test chamber air temperature is 38 ± 3 °C, relative humidity is 50 ± 10%, and drying time is 1440 hours. The product of the invention described in this application retains good tensile strength even after aging, extending the service life of the product.
[0007] Chinese Patent Publication No. CN115537959A relates to a composite material characterized by containing polyethylene as a raw material, having a shrinkage rate R of 0.2 to 0.7, a standard heat shrinkage strength σr of 0.5 to 3.5 N / mm2, and a mold resistance rating lower than Grade 2. This application has been widely applied because it has good shrinkage performance and desirable antibacterial and antifungal effects.
[0008] Chinese Patent Publication No. CN109154138A relates to a composite laminate which is a composite material including a nonwoven vapor-permeable sheet, the composite laminate comprising at least one water vapor-permeable nonwoven sheet having first and second surfaces, and a fluorinated polymer coating on the first surface of the sheet, wherein (i) the fluorinated polymer coating is present in such an amount that the total fluorine content of the coated nonwoven sheet is between 0.05 gsm and 0.4 gsm or less, and (ii) the composite laminate exhibits a retaining water pressure head of at least 60% after exposure to wet wood.
[0009] U.S. Patent Publication No. US20160138197A1 relates to a flash-spun plexifila yarn and sheet with a BET surface area of 12 m². 2 Regarding flash-spun plexifila fiber bundles with a grinding value of less than / g, the bundle has a grinding value of at least 0.9 mm / g, wherein the fiber bundle comprises fibers mainly formed from polyethylene, the fibers have a total crystallinity index less than 55%, and the fiber bundle has a sheet with a break elongation greater than 55%.
[0010] U.S. Patent Publication No. US8048513 relates to a flash-spun sheet and an improved plexifila sheet used in protective clothing and filter media, wherein the material consists of substantially continuous polyethylene plexifila sheet fiber bundles and is standardized to 1.0 ounce / yard with a density of at least 2 cfm / ft 2 It has a frazer transmittance of [value missing].
[0011] Conventional technologies have limited research on the heat shielding and haze performance of flash evaporation materials, and flash evaporation materials have the problem of deteriorating heat shielding and haze performance after a certain period of use. [Overview of the Initiative] [Problems that the invention aims to solve]
[0012] The present invention aims to provide a flash evaporation material with a low haze decay rate to address the above-mentioned problems. [Means for solving the problem]
[0013] To achieve the above objective, the present invention employs the following technical solutions: This flash evaporation material has a low haze attenuation rate, and the raw materials for the flash evaporation material include polyethylene, with a basis weight of 35 g / m² of the flash spun nonwoven fabric. 2 Larger than, The work of compression P of the flash evaporation material is 0.07 gf·cm / cm 2 Larger than, The compression ratio work was tested by a KES style tester, and the compression ratio work was tested by an FB3. The haze decay rate ΔW of flash evaporation materials is 0.3% to 1.5%. △W=(W0-W5) / W0*100%, The attenuation rate ΔS of the heat shielding rate of flash evaporation materials is 7% to 15%. △S = (S0 - S5) / S0 * 100% The tests for heat shielding rate, haze, and lateral tensile strength were as follows: (1) The sample was left for 24 hours under conditions of 25°C and 65% relative humidity, and its light shielding index was measured and recorded as the initial heat shielding rate S0, its haze was measured and recorded as the initial haze W0, and its lateral tensile strength was measured and recorded as the lateral tensile strength CTS0. (2) Then, after being exposed to a dry heat atmosphere at 90°C for 6 hours, and then cooled for 24 hours under conditions of 25°C and 65% relative humidity, (3) Repeat the operation of step (2), perform four more treatments, then measure its light shielding index and record it as the final heat shielding rate S5, measure its haze and record it as the final haze W5, measure its transverse tensile strength and record it as the final transverse tensile strength CTS5, Haze is tested in accordance with the national standard GB / T2410-2008, The heat shielding rate is tested based on the measurement of the national standard GB / T41560-2022, characterized in that, the flash evaporation material has a low haze attenuation rate.
[0014] The tensile strength is tested in accordance with the national standard GB / T12914-2018, and the tensile strength is the maximum tension that a specimen per unit width can withstand before breaking under specified test conditions.
[0015] The basis weight of the flash-spun nonwoven fabric is 75 g / m 2 less than.
[0016] The basis weight of the flash-spun nonwoven fabric is 65 g / m 2 less than.
[0017] The compression specific work P of the flash-spun nonwoven fabric is 0.15 gf·cm / cm 2 greater than.
[0018] The compression specific work P of the flash-spun nonwoven fabric is 2 gf·cm / cm 2 less than.
[0019] The compression specific work P of the flash-spun nonwoven fabric is 1 gf·cm / cm 2 less than.
[0020] The haze attenuation rate ΔW of the flash evaporation material is 0.6%~0.9%.
[0021] The haze attenuation rate ΔW of the flash evaporation material is 0.9%~1.3%.
[0022] The attenuation rate of the heat shielding rate of the flash evaporation material is 7%~10%.
[0023] The attenuation rate of the heat shielding coefficient of flash evaporation materials is 10% to 14%.
[0024] The lateral tensile strength attenuation rate (ΔCTS) of flash evaporation materials is 2% to 10%. △CTS=(CTS0-CTS5) / CTS0*100%, The tensile strength in the lateral direction, CTS0, is greater than 1.4 kN / m.
[0025] The lateral tensile strength attenuation rate (ΔCTS) of flash evaporation materials is 3% to 5%.
[0026] The lateral tensile strength attenuation rate (ΔCTS) of flash evaporation materials is 5% to 7%.
[0027] The lateral tensile strength attenuation rate (ΔCTS) of flash evaporation materials is 7% to 9%.
[0028] A method for preparing a flash evaporation material with a low haze decay rate, comprising the preparation of a spinning solution and the preparation of a flash evaporation material, Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of porous carbon material supporting zinc oxide in the spinning raw material is 3% to 6%. A method for preparing a porous carbon material supported with zinc oxide, comprising the following specific technical steps: (i) A step of preparing a solution in which the surface of silica nanoparticles is coated with polyvinyl alcohol, Silica nanoparticles are added to deionized water and ultrasonically dispersed to obtain a dispersion. Polyvinyl alcohol powder is then added to the dispersion and stirred while simultaneously heating, controlling the heating temperature to 80°C to 100°C to dissolve and disperse the powder. After the polyvinyl alcohol solution has dissolved, the reaction is carried out for 36 to 60 hours. Undissolved polyvinyl alcohol is then removed by filtration to obtain a coating solution, resulting in a solution in which the surface of the silica nanoparticles is coated with polyvinyl alcohol. In the step, the mass ratio of silica nanoparticles to polyvinyl alcohol powder is 1:9 to 1:12. (ii) A step of preparing a zinc-containing porous carbon precursor dispersion, The solution in which the surface of the silica nanoparticles prepared in step (1) is coated with polyvinyl alcohol is added to the zinc nitrate aqueous solution to continue the primary reaction, and the zinc and polyvinyl alcohol are chelated and supported on the surface of the silica nanoparticles. Then, the pH of the mixed solution is slowly adjusted to 11-12 with alkali, and the secondary reaction is continued under alkaline conditions to obtain a zinc-containing porous carbon precursor dispersion. The primary reaction time is 30 to 48 hours, and the reaction temperature is 60°C to 80°C. The alkali may specifically be a 0.1 mol / L sodium hydroxide solution or a potassium hydroxide solution. The secondary reaction was carried out under alkaline conditions, with a reaction time of 4 to 8 hours. This step involves etching the internal silica while simultaneously generating zinc hydroxide precipitate from the internal zinc ions in an alkaline solution, thereby achieving both silica etching and zinc hydroxide precipitate formation simultaneously. (iii) A step of preparing a porous carbon material supported with zinc oxide, Finally, the zinc-containing porous carbon precursor dispersion from step (2) is centrifuged, and the lower precipitate is taken to obtain the zinc-containing porous carbon precursor. The lower zinc-containing porous carbon precursor is then calcined with oxygen at 180°C to 200°C for 15 to 30 minutes, and then rapidly heated to 440°C to 450°C within 1 to 5 minutes, followed by oxygen-free calcination for 45 to 60 minutes. After natural cooling, a porous carbon material supporting zinc oxide is obtained. Includes.
[0029] In the firing process, first, aerobic firing is performed, and the polyvinyl alcohol structure undergoes aerobic pre-oxidation carbonization under conditions of 180°C. After the zinc hydroxide oxidatively decomposes to produce zinc oxide, the process then moves to high-temperature oxygen-free carbonization. Under an oxygen-free environment, the formed carbon material and zinc oxide undergo an oxidation-reduction reaction, ultimately producing excellent zinc oxide. This avoids the conventional problems of blend addition and dispersion. The zinc oxide is substituted and reduced on the surface of the carbon material, forming a relatively stable zinc oxide-doped porous carbon structure. The zinc oxide-doped porous carbon structure fills the gaps in the flash evaporation fibers of the flash evaporation material, reducing light transmission and increasing light emission and refraction. Furthermore, zinc oxide has good emission performance, thereby improving the heat shielding performance of the product.
[0030] Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 500 ppm to 2000 ppm.
[0031] The surfactant is polyvinylpyrrolidone.
[0032] The solvents include aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, and similar substances.
[0033] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0034] The flash evaporation spinning temperature is 200°C to 220°C. The hot press temperature is 105°C to 115°C. [Effects of the Invention]
[0035] Compared to conventional technologies, the superior effects of the present invention are as follows: The present invention experimentally found that the haze decay rate and heat shielding decay rate of flash evaporation materials are closely related to factors such as the content of zinc oxide-supported porous carbon material in the spinning raw material and the content of surfactant in the spinning solvent. Furthermore, the present invention provides a novel flash evaporation material manufacturing process so that the prepared flash evaporation material has a lower haze decay rate and heat shielding decay rate, thereby overcoming the problem in the prior art that flash evaporation materials show a clear decrease in heat shielding performance and haze performance after being used for a certain period of time. [Modes for carrying out the invention]
[0036] The present invention will be described in more detail below with reference to specific embodiments.
[0037] Example 1 This embodiment provides a flash evaporation material with a low haze decay rate, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of the porous carbon material supporting zinc oxide in the spinning raw material is 3%. A method for preparing a porous carbon material supported with zinc oxide, comprising the following specific technical steps: (i) A step of preparing a solution in which the surface of silica nanoparticles is coated with polyvinyl alcohol, Silica nanoparticles are added to deionized water and ultrasonically dispersed to obtain a dispersion. Polyvinyl alcohol powder is then added to the dispersion and stirred while simultaneously heating, controlling the heating temperature to 80°C to 100°C to dissolve and disperse the powder. After the polyvinyl alcohol solution has dissolved, the reaction is carried out for 36 to 60 hours. Undissolved polyvinyl alcohol is then removed by filtration to obtain a coating solution, resulting in a solution in which the surface of the silica nanoparticles is coated with polyvinyl alcohol. In the step, the mass ratio of silica nanoparticles to polyvinyl alcohol powder is 1:9. (ii) A step of preparing a zinc-containing porous carbon precursor dispersion, The solution in which the surface of the silica nanoparticles prepared in step (1) is coated with polyvinyl alcohol is added to the zinc nitrate aqueous solution to continue the primary reaction, and the zinc and polyvinyl alcohol are chelated and supported on the surface of the silica nanoparticles. Then, the pH of the mixed solution is slowly adjusted to 11-12 with alkali, and the secondary reaction is continued under alkaline conditions to obtain a zinc-containing porous carbon precursor dispersion. The primary reaction time was 30 hours, and the reaction temperature was 60°C to 80°C. The alkali may specifically be a 0.1 mol / L sodium hydroxide solution or a potassium hydroxide solution. The secondary reaction was carried out under alkaline conditions, and the reaction time was 5 hours. This step involves etching the internal silica while simultaneously generating zinc hydroxide precipitate from the internal zinc ions in an alkaline solution, thereby achieving both silica etching and zinc hydroxide precipitate formation simultaneously. (iii) A step of preparing a porous carbon material supported with zinc oxide, Finally, the zinc-containing porous carbon precursor dispersion from step (2) is centrifuged, and the lower precipitate is taken to obtain the zinc-containing porous carbon precursor. The lower zinc-containing porous carbon precursor is then aerobically calcined at 180°C to 200°C for 15 to 30 minutes, and then rapidly heated to 440°C to 450°C within 1 to 5 minutes, followed by oxygen-free calcination for 45 to 60 minutes. After natural cooling, a porous carbon material supporting zinc oxide is obtained.
[0038] Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 700 ppm.
[0039] The surfactant is polyvinylpyrrolidone.
[0040] The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0041] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0042] The flash evaporation spinning temperature is 200°C. The hot press temperature is 105°C.
[0043] The performance test data for the flash evaporation material prepared in this embodiment are shown in Table 1.
[0044] Example 2 This embodiment provides a flash evaporation material with a low haze decay rate, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of the porous carbon material supporting zinc oxide in the spinning raw material is 4.5%. A method for preparing a porous carbon material supported with zinc oxide, comprising the following specific technical steps: (i) A step of preparing a solution in which the surface of silica nanoparticles is coated with polyvinyl alcohol, Silica nanoparticles are added to deionized water and ultrasonically dispersed to obtain a dispersion. Polyvinyl alcohol powder is then added to the dispersion and stirred while simultaneously heating, controlling the heating temperature to 80°C to 100°C to dissolve and disperse the powder. After the polyvinyl alcohol solution has dissolved, the reaction is carried out for 36 to 60 hours. Undissolved polyvinyl alcohol is then removed by filtration to obtain a coating solution, resulting in a solution in which the surface of the silica nanoparticles is coated with polyvinyl alcohol. In the step, the mass ratio of silica nanoparticles to polyvinyl alcohol powder is 1:10.5. (ii) A step of preparing a zinc-containing porous carbon precursor dispersion, The solution in which the surface of the silica nanoparticles prepared in step (1) is coated with polyvinyl alcohol is added to the zinc nitrate aqueous solution to continue the primary reaction, and the zinc and polyvinyl alcohol are chelated and supported on the surface of the silica nanoparticles. Then, the pH of the mixed solution is slowly adjusted to 11-12 with alkali, and the secondary reaction is continued under alkaline conditions to obtain a zinc-containing porous carbon precursor dispersion. The primary reaction time was 40 hours, and the reaction temperature was 60°C to 80°C. The alkali may specifically be a 0.1 mol / L sodium hydroxide solution or a potassium hydroxide solution. The secondary reaction was carried out under alkaline conditions, and the reaction time was 6 hours. This step involves etching the internal silica while simultaneously generating zinc hydroxide precipitate from the internal zinc ions in an alkaline solution, thereby achieving both silica etching and zinc hydroxide precipitate formation simultaneously. (iii) A step of preparing a porous carbon material supported with zinc oxide, Finally, the zinc-containing porous carbon precursor dispersion from step (2) is centrifuged, and the lower precipitate is taken to obtain the zinc-containing porous carbon precursor. The lower zinc-containing porous carbon precursor is then aerobically calcined at 180°C to 200°C for 15 to 30 minutes, and then rapidly heated to 440°C to 450°C within 1 to 5 minutes, followed by oxygen-free calcination for 45 to 60 minutes. After natural cooling, a porous carbon material supporting zinc oxide is obtained.
[0045] Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 1200 ppm.
[0046] The surfactant is polyvinylpyrrolidone.
[0047] The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0048] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0049] The flash evaporation spinning temperature is 210°C. The hot press temperature is 110°C.
[0050] The performance test data for the flash evaporation material prepared in this embodiment are shown in Table 1.
[0051] Example 3 This embodiment provides a flash evaporation material with a low haze decay rate, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of the porous carbon material supporting zinc oxide in the spinning raw material is 6%. A method for preparing a porous carbon material supported with zinc oxide, comprising the following specific technical steps: (i) A step of preparing a solution in which the surface of silica nanoparticles is coated with polyvinyl alcohol, Silica nanoparticles are added to deionized water and ultrasonically dispersed to obtain a dispersion. Polyvinyl alcohol powder is then added to the dispersion and stirred while simultaneously heating, controlling the heating temperature to 80°C to 100°C to dissolve and disperse the powder. After the polyvinyl alcohol solution has dissolved, the reaction is carried out for 36 to 60 hours. Undissolved polyvinyl alcohol is then removed by filtration to obtain a coating solution, resulting in a solution in which the surface of the silica nanoparticles is coated with polyvinyl alcohol. In the step, the mass ratio of silica nanoparticles to polyvinyl alcohol powder is 1:12. (ii) A step of preparing a zinc-containing porous carbon precursor dispersion, The solution in which the surface of the silica nanoparticles prepared in step (1) is coated with polyvinyl alcohol is added to the zinc nitrate aqueous solution to continue the primary reaction, and the zinc and polyvinyl alcohol are chelated and supported on the surface of the silica nanoparticles. Then, the pH of the mixed solution is slowly adjusted to 11-12 with alkali, and the secondary reaction is continued under alkaline conditions to obtain a zinc-containing porous carbon precursor dispersion. The primary reaction time was 48 hours, and the reaction temperature was 60°C to 80°C. The alkali may specifically be a 0.1 mol / L sodium hydroxide solution or a potassium hydroxide solution. The secondary reaction was carried out under alkaline conditions, and the reaction time was 8 hours. This step involves etching the internal silica while simultaneously generating zinc hydroxide precipitate from the internal zinc ions in an alkaline solution, thereby achieving both silica etching and zinc hydroxide precipitate formation simultaneously. (iii) A step of preparing a porous carbon material supported with zinc oxide, Finally, the zinc-containing porous carbon precursor dispersion from step (2) is centrifuged, and the lower precipitate is taken to obtain the zinc-containing porous carbon precursor. The lower zinc-containing porous carbon precursor is then aerobically calcined at 180°C to 200°C for 15 to 30 minutes, and then rapidly heated to 440°C to 450°C within 1 to 5 minutes, followed by oxygen-free calcination for 45 to 60 minutes. After natural cooling, a porous carbon material supporting zinc oxide is obtained.
[0052] Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 2000 ppm.
[0053] The surfactant is polyvinylpyrrolidone.
[0054] The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0055] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0056] The flash evaporation spinning temperature is 220°C. The hot press temperature is 115°C.
[0057] The performance test data for the flash evaporation material prepared in this embodiment are shown in Table 1.
[0058] Comparative Example 1 This comparative example provides a flash evaporation material, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The raw material for spinning is polyethylene. Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 1200 ppm.
[0059] The surfactant is polyvinylpyrrolidone.
[0060] The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0061] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0062] The flash evaporation spinning temperature is 210°C. The hot press temperature is 110°C.
[0063] The performance test data for the flash evaporation material prepared in this comparative example are shown in Table 1.
[0064] Comparative Example 2 This comparative example provides a flash evaporation material, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of the porous carbon material supporting zinc oxide in the spinning raw material is 1%. The method for preparing the porous carbon material supported with zinc oxide is the same as in Example 2.
[0065] Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 1200 ppm.
[0066] The surfactant is polyvinylpyrrolidone.
[0067] The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0068] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0069] The flash evaporation spinning temperature is 210°C. The hot press temperature is 110°C.
[0070] The performance test data for the flash evaporation material prepared in this comparative example are shown in Table 1.
[0071] Comparative Example 3 This comparative example provides a flash evaporation material, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of the porous carbon material supporting zinc oxide in the spinning raw material is 2%. The method for preparing the porous carbon material supported with zinc oxide is the same as in Example 2.
[0072] Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 1200 ppm.
[0073] The surfactant is polyvinylpyrrolidone.
[0074] The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0075] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0076] The flash evaporation spinning temperature is 210°C. The hot press temperature is 110°C.
[0077] The performance test data for the flash evaporation material prepared in this comparative example are shown in Table 1.
[0078] Comparative Example 4 This comparative example provides a flash evaporation material, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of the porous carbon material supporting zinc oxide in the spinning raw material is 8%. The method for preparing the porous carbon material supported with zinc oxide is the same as in Example 2.
[0079] Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 1200 ppm.
[0080] The surfactant is polyvinylpyrrolidone.
[0081] The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0082] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0083] The flash evaporation spinning temperature is 210°C. The hot press temperature is 110°C.
[0084] The performance test data for the flash evaporation material prepared in this comparative example are shown in Table 1.
[0085] Comparative Example 5 This comparative example provides a flash evaporation material, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of the porous carbon material supporting zinc oxide in the spinning raw material is 9%. The method for preparing the porous carbon material supported with zinc oxide is the same as in Example 2.
[0086] Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 1200 ppm.
[0087] The surfactant is polyvinylpyrrolidone.
[0088] The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0089] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0090] The flash evaporation spinning temperature is 210°C. The hot press temperature is 110°C.
[0091] The performance test data for the flash evaporation material prepared in this comparative example are shown in Table 1.
[0092] Comparative Example 6 This comparative example provides a flash evaporation material, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of the porous carbon material supporting zinc oxide in the spinning raw material is 4.5%. The method for preparing the porous carbon material supported with zinc oxide is the same as in Example 2. Spinning solvent is a solvent, The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0093] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0094] The flash evaporation spinning temperature is 210°C. The hot press temperature is 110°C.
[0095] The performance test data for the flash evaporation material prepared in this comparative example are shown in Table 1.
[0096] Comparative Example 7 This comparative example provides a flash evaporation material, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of the porous carbon material supporting zinc oxide in the spinning raw material is 4.5%. The method for preparing the porous carbon material supported with zinc oxide is the same as in Example 2. Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 200 ppm.
[0097] The surfactant is polyvinylpyrrolidone.
[0098] The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0099] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0100] The flash evaporation spinning temperature is 210°C. The hot press temperature is 110°C.
[0101] The performance test data for the flash evaporation material prepared in this comparative example are shown in Table 1.
[0102] Comparative Example 8 This comparative example provides a flash evaporation material, which mainly involves the preparation of a spinning solution and the preparation of a flash evaporation material. Here, The preparation of the spinning solution is as follows: the spinning raw material is dissolved in the spinning solvent to obtain the spinning solution. The spinning raw materials are polyethylene and a porous carbon material supported with zinc oxide. The mass fraction of the porous carbon material supporting zinc oxide in the spinning raw material is 4.5%. The method for preparing the porous carbon material supported with zinc oxide is the same as in Example 2.
[0103] Spinning solvents are surfactants and solvents. The surfactant is present in the spinning solvent at a concentration of 2000 ppm.
[0104] The surfactant is polyvinylpyrrolidone.
[0105] The solvents are chloroethane, dichloromethane, 1,1-dichloro-2,2-difluoroethane, and 1,1,2,2,3,3,4,4-octafluorobutane, with a mass ratio of 4:4:1:1.
[0106] The preparation of the flash evaporation material is as follows: The prepared spinning solution is placed in the spinning chamber and flash evaporation spinning is performed to obtain flash evaporation fibers through the nozzle of the spinning assembly. Then, the flash evaporation fibers are subjected to a web formation and hot pressing process to obtain flash evaporation material.
[0107] The flash evaporation spinning temperature is 210°C. The hot press temperature is 110°C.
[0108] The performance test data for the flash evaporation material prepared in this comparative example are shown in Table 1. JPEG0007934050000001.jpg93170
[0109] Analysis of Results: Comparing the above data, it can be seen that increasing the amount of porous carbon material supported with zinc oxide in the spinning raw material reduces the haze attenuation rate and the heat shielding rate attenuation rate, but beyond a certain point, the rate of reduction clearly slows down. Increasing the amount of surfactant used in the spinning solvent also reduces the haze attenuation rate and the heat shielding rate attenuation rate, but beyond a certain point, the rate of reduction also clearly slows down.
[0110] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments, or substitute them in similar ways, without departing from the spirit of the invention or exceeding the scope defined in the appended claims.
Claims
1. A flash evaporation material with a low haze attenuation rate, wherein the raw materials of the flash evaporation material include polyethylene, and the basis weight of the flash spun nonwoven fabric is 35 g / m². 2 Larger than, The work of compression ratio P of the flash evaporation material is 0.07 gf·cm / cm 2 Larger than, The compression ratio work P is a value measured by a KES style tester. The haze decay rate ΔW of the flash evaporation material is 0.3% to 1.5%. △W = (W 0 -W 5 ) / W 0 *100% The attenuation rate ΔS of the heat shielding rate of flash evaporation material is 7% to 15%. △S = (S 0 -S 5 ) / S 0 *100% The aforementioned W 0 , W 5 , S 0 and S5 are values measured by the following methods, (1) After leaving the sample at 25°C and 65% relative humidity for 24 hours, the haze was measured according to GB / T2410-2008 to determine the initial haze W 0 Based on GB / T41560-2022, the heat shielding rate was measured to determine the initial heat shielding rate S. 0 year, (2) Exposing the sample to a dry atmosphere at 90°C for 6 hours, and then cooling it for 24 hours under conditions of 25°C and 65% relative humidity constitutes one treatment. (3) After performing the above process a total of five times, the haze is measured according to GB / T2410-2008 to obtain the final haze W5, and the heat shielding rate is measured according to GB / T41560-2022 to obtain the final heat shielding rate S 5 Let it be, A flash evaporation material characterized by a low haze decay rate.
2. The basis weight of the flash-spun nonwoven fabric is 75 g / m². 2 A flash evaporation material with a low haze decay rate according to claim 1, characterized in that it is smaller than the specified value.
3. The compression ratio work P of the flash-spun nonwoven fabric is 0.15 gf·cm / cm 2 A flash evaporation material with a low haze decay rate according to claim 1, characterized in that it is greater than the above.
4. The flash evaporation material with a low haze decay rate according to claim 1, characterized in that the haze decay rate ΔW of the flash evaporation material is 0.6% to 0.9%.
5. The flash evaporation material with a low haze decay rate according to claim 1, characterized in that the haze decay rate ΔW of the flash evaporation material is 0.9% to 1.3%.
6. The flash evaporation material with low haze attenuation rate according to claim 1, characterized in that the attenuation rate of the heat shielding rate of the flash evaporation material is 7% to 10%.
7. The flash evaporation material with low haze attenuation rate according to claim 1, characterized in that the attenuation rate of the heat shielding rate of the flash evaporation material is 10% to 14%.
8. The lateral tensile strength attenuation rate (ΔCTS) of the flash evaporation material is 2% to 10%. △CTS = (CTS 0 -CTS 5 ) / CTS 0 *100% Transverse tensile strength (CTS) 0 It is greater than 1.4 kN / m, The CTS 0 This is the lateral tensile strength measured according to GB / T12914-2018 after the sample has been left for 24 hours under conditions of 25°C and 65% relative humidity. The CTS 5 This refers to the lateral tensile strength measured according to GB / T12914-2018 after the sample has been subjected to a treatment process of exposing it to a dry heat atmosphere at 90°C for 6 hours, followed by cooling it under conditions of 25°C and 65% relative humidity for 24 hours, a total of five times. The flash evaporation material with low haze decay rate according to feature 1.
9. The flash evaporation material with low haze attenuation rate according to claim 8, characterized in that the lateral tensile strength attenuation rate ΔCTS of the flash evaporation material is 3% to 5%.
10. The flash evaporation material with low haze attenuation rate according to claim 8, characterized in that the lateral tensile strength attenuation rate ΔCTS of the flash evaporation material is 5% to 7%.
11. The flash evaporation material with low haze decay rate according to claim 1, characterized in that the spinning raw material is a porous carbon material supported with polyethylene and zinc oxide, and the spinning solvent is a surfactant and a solvent.
12. The mass fraction of porous carbon material supporting zinc oxide in the spinning raw material is 3% to 6%. The low haze attenuation flash evaporation material according to claim 11, characterized in that the surfactant is present in a concentration of 500 ppm to 2000 ppm in the spinning solvent.
13. A method for producing a flash evaporation material with a low haze decay rate according to claim 12, A spinning solution preparation step involves dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, The process includes: placing the spinning solution into a spinning chamber and performing flash evaporation spinning to obtain flash evaporation fibers using a nozzle of a spinning assembly; and obtaining flash evaporation material by web formation and hot pressing processes using the flash evaporation fibers. The aforementioned spinning raw material is a porous carbon material supporting polyethylene and zinc oxide. The porous carbon material supporting the zinc oxide is (1) A step of preparing a solution in which the surface of silica nanoparticles is coated with polyvinyl alcohol, (ii) A step of adding a solution in which the surface of the silica nanoparticles is coated with polyvinyl alcohol to an aqueous zinc nitrate solution to carry out a primary reaction, adjusting the pH of the mixed solution to 11-12 with alkali, and carrying out a secondary reaction under alkaline conditions to obtain a zinc-containing porous carbon precursor dispersion, (iii) The zinc-containing porous carbon precursor dispersion is centrifuged to obtain a zinc-containing porous carbon precursor, the zinc-containing porous carbon precursor is aerobically calcined at 180°C to 200°C for 15 to 30 minutes, the temperature is raised to 440°C to 450°C within 1 to 5 minutes, the carbon-free is calcined for 45 to 60 minutes, and then allowed to cool naturally. Prepared by, A method for manufacturing flash evaporation materials with low haze decay.
Citation Information
Patent Citations
Flash fabric with low compression ratio work
CN116356482A
Packaging material for various medicines
JP1993124675A
Deodorizing, anti-fungous and purifying material
JP1996299420A
Antimicrobial aggregate of fiber, method for producing the same and its application
JP2007077519A